Psychosis or Mystical Religious Experience? A New Paradigm Grounded in Psychology and Reformed Theology - DeHoff, Susan L. (Springer International Publishing, 2018)
This book presents a new paradigm for distinguishing psychotic and mystical religious experiences. In order to explore how Presbyterian pastors differentiate such events, Susan L. DeHoff draws from Reformed theology, psychological theory, and robust qualitative research. Following a conversation among multidisciplinary voices, she presents a new paradigm considering the similarities, differences, and possible overlap of psychotic and mystical religious experiences.